Chronic uranium contamination alters spinal motor neuron integrity via modulation of SMN1 expression and microglia recruitment. (8th July 2016) - Saint-Marc, Brice; Elie, Christelle; Manens, Line; Tack, Karine; Benderitter, Marc; Gueguen, Yann; Ibanez, Chrystelle
Highlights: Uranium contamination induces a decrease of motor neuron number in rat spinal cord. Uranium contamination induces a decrease of expression of the survival protein SMN1. Uranium contamination increases the number of microglial cells in rat spinal cord. Results suggest potential overexpression of MCP-1 by motor neurons themselves. Results suggest the trigger of a neuroinflammation process. Abstract: Consequences of uranium contamination have been extensively studied in brain as cognitive function impairments were observed in rodents. Locomotor disturbances have also been described in contaminated animals. Epidemiological studies have revealed increased risk of motor neuron diseases in veterans potentially exposed to uranium during their military duties. To our knowledge, biological response of spinal cord to uranium contamination has not been studied even though it has a crucial role in locomotion. Four groups of rats were contaminated with increasing concentrations of uranium in their drinking water compared to a control group to study cellular mechanisms involved in locomotor disorders. Nissl staining of spinal cord sections revealed the presence of chromatolytic neurons in the ventral horn. This observation was correlated with a decreased number of motor neurons in the highly contaminated group and a decrease of SMN1 protein expression (Survival of Motor Neuron 1). While contamination impairs motor neuron integrity, an increasing number of microglial cells indicates the trigger of a neuroinflammation process. Potential overexpression of a microglial recruitment chemokine, MCP-1 (Monocyte Chimioattractant Protein 1), by motor neurons themselves could mediate this process. Studies on spinal cord appear to be relevant for risk assessment of population exposed via contaminated food and water.